2006
DOI: 10.1021/jf062422j
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Structure−Activity Relationship Study of Bitter Peptides

Abstract: A database consisting of 224 di- to tetradecapeptides and five amino acids was compiled to study quantitative structure-activity relationships of bitter peptides. Partial least-squares regression-1 analysis was conducted using the amino acid three z-scores and/or three parameters (total hydrophobicity, residue number, and log mass values) as X-variables and bitterness values (log 1/T where T is the bitterness threshold) as Y-variables. Using the three parameters only, significant models (p < 0.001) were obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
102
2
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(113 citation statements)
references
References 44 publications
(81 reference statements)
7
102
2
2
Order By: Relevance
“…25 The molecular mass, hydrophobicity, number of amino acid residues in the peptide together with the amino acid descriptors of the 3-z scale were incorporated in a PLSR. The previous physicochemical parameters had a higher inuence on the bitterness than the 3-z scale.…”
Section: 24mentioning
confidence: 99%
“…25 The molecular mass, hydrophobicity, number of amino acid residues in the peptide together with the amino acid descriptors of the 3-z scale were incorporated in a PLSR. The previous physicochemical parameters had a higher inuence on the bitterness than the 3-z scale.…”
Section: 24mentioning
confidence: 99%
“…The bitter taste of protein hydrolysates limits their utilization for human consumption. It is reported that the bitter taste of protein hydrolysates is mainly caused by hydrophobic amino acid residues and oligopeptides, and therefore the specificity of the enzyme used is decisive for the amount of such peptides produced during hydrolysis (Kim and Li-Chan, 2006;Gildberg et al, 2002). As shown in Fig.3c, flavourzyme hydrolysates, a fungal complex of exopeptidases and endoproteases used in the food functionality industry for extensive hydrolysis of proteins, display the least bitter taste in contrast to all the other enzymes.…”
Section: Selection Of Enzyme For Enzymatic Hydrolysismentioning
confidence: 99%
“…A current drawback with production of protein hydrolysates is the formation of bitter and unpalatable tastes generated during the hydrolysis process. Bitter taste is mainly ascribed to small peptides of less than 1000 Da with hydrophobic and/or aromatic amino acids [65]. Not only the presence of hydrophobic and aromatic amino acids, but also the amino acid peptide sequence is important for the bitter taste intensity.…”
Section: Food Ingredientsmentioning
confidence: 99%